Exploring Applications of Lagranges Equations in Technology: A Systematic Literature Review - Damayanti, Fitria Siska; Noviana, RA Sania; Lestari, Yora Inda; Akhsan, Hamdi; Ismet, Ismet (Graduate School of Universitas Syiah Kuala, 2024)
Lagrange's equation is a formula in analytical mechanics used to solve problems with physical system dynamics. It allows mathematical modeling to simplify complex mechanical problems by changing the coordinate system, thus providing a deeper understanding of motion. In this research, a literature study was conducted using the Systemic Literature Review (SLR) method from 30 data sources, 24 of which were indexed by Scopus. A total of 11 articles have been reviewed with a focus on the application of Lagrange's equation in various technologies. The review results show that Lagrange multipliers provide a powerful tool for optimizing energy flow within complex smart grids. The benefits extend beyond smart grids. Lagrange's equations are a powerful mathematical tool applicable to various engineering challenges that involve finding optimal solutions under constraints.